2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24559
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Misconceptions of Industrial Engineering from First-year Engineering Students

Abstract: Perception has a hidden importance in our society. It is what drives us to buy that name brand product, move to a certain area of town, or even select a university to call home. The U.S. News & World Report even uses it for rankings, but in today's growing, diverse environment, perception is constantly changing; it is often developed from an individual's experiences and their surrounding environment. It itself is a form of bias. Therefore, it is important to collect, track how it changes, and understand the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, engineering students may not have a clear idea of the working world, or of what their careers will entail (Rouvrais and Chelin 2010;Berglund and Heintz 2014;IESF 2016b). It is critical to gain insight into the perceptions of engineering students so that engineering schools impart correct knowledge to both industry and students (Specking, Kirkwood, and Yang 2015;Jones et al 2010). Similarly, the research of Kinnunen et al (2016) in computer science education also stressed the importance of examining the career expectations of students in order better to equip them.…”
Section: Factors Affecting Career Choices Of Engineering Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, engineering students may not have a clear idea of the working world, or of what their careers will entail (Rouvrais and Chelin 2010;Berglund and Heintz 2014;IESF 2016b). It is critical to gain insight into the perceptions of engineering students so that engineering schools impart correct knowledge to both industry and students (Specking, Kirkwood, and Yang 2015;Jones et al 2010). Similarly, the research of Kinnunen et al (2016) in computer science education also stressed the importance of examining the career expectations of students in order better to equip them.…”
Section: Factors Affecting Career Choices Of Engineering Studentsmentioning
confidence: 99%
“…In spite of such a favourable context, graduate students are, however, not always adequately prepared to enter the workplace (Ramadi, Ramadi, and Nasr 2016;Llorens et al 2013;Rodrigues 2001); and their conceptions may not correspond to the offers of real professional practices. Research has also illustrated the importance of analysing engineering students' perceptions of their future careers (Dias 2011;Gokuladas 2010;Specking, Kirkwood, and Yang 2015;Kinnunen et al 2016;Jones et al 2010;Ngambeki, Dalrymple, and Evangelou 2009). As argued by Baytiyeh and Naja (2011), much care should be taken in deciding on a job that leads to sustainable professional and personal growth and financial well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial engineering further complicates these difficulties since so few students have any preexisting understanding of industrial engineering principles and often have misconceptions. [6] Capobianco et al found that students asked to picture an engineer describe a mechanic, laborer, or technician. [7] Industrial engineers fit this mold even less than other branches of engineering, making direct and effective industrial engineering outreach projects imperative.…”
Section: Introductionmentioning
confidence: 99%
“…The faculty survey received 10 responses, a 40% response rate, from industrial engineering faculty (56 total faculty survey responses), while the alumni and industry partner survey received 143 responses from industrial engineering alumni and industry partners (502 total responses). 1 Due to incomplete responses for the main questions of this study, a lower number of responses will be analyzed (8 faculty and 69 alumni/industry partners). This study utilizes 7 of the 15 questions from the faculty, industry partners, and alumni surveys, as seen below.…”
mentioning
confidence: 99%